Editorial Board and Guidelines for the Authors - Journal, Editor (ASPENSI in Bandung, Indonesia, 2016)
TAWARIKH will provide a peer-reviewed forum for the publication of thought-leadership articles, briefings, discussion, applied research, case and comparative studies, expert comment and analysis on the key issues surrounding the history education and historical studies, and its various aspects. Analysis will be practical and rigorous in nature.Bandung, Indonesia: October 28, 2016.Sincerely yours,Andi Suwirta, M.Hum.Chairperson of ASPENSI; and Senior Lecturer at the Department of History Education FPIPS UPI in Bandung, West Java, Indonesia.Â